Prevalence and Management of Hypokalemia in Peritoneal Dialysis Patients in Qatar - Abdullah Hamad; Mohammed Ezzat Hussain; Shaza Elsanousi; Hanaa Ahmed; Luzvi Navalta; Vimala Lonappan; Fadwa Alali (International Journal of Nephrology)
Introduction. Hypokalemia is common in patients undergoing peritoneal dialysis (PD). It is associated with increased cardiovascular and all-cause mortality. Treatment usually includes oral potassium supplements, which are poorly tolerated. Our aim was to evaluate the prevalence of hypokalemia in PD patients in Qatar and to improve treatment measures. Methods. All PD patients in Qatar with persistent hypokalemia and on potassium supplement were included. We performed a root cause analysis, and a management pathway was created. We collected data before (Period 1) and after (Period 2) implementation of the new pathway. Results. A total of 143 patients with a mean age of 54 years (range 21–82 years) were included in the study. Initial results of Period 1 showed hypokalemia in 48 patients (34%); of these, 14 (29%) had hypomagnesemia. Hypokalemia resolved in 10 of the patients after correction of their hypomagnesemia. The remaining 4 patients continued to require potassium supplementation despite correction of their hypomagnesemia. We started spironolactone (25 mg daily) in 13 of the hypokalemia patients. After 3 months, their mean serum potassium level improved from 3.2 ± 0.3 mmol/L to 3.9 ± 0.4 mmol/L (p<0.001), and the prevalence of patients with persistent hypokalemia decreased from 36% to 21% (statistically significant with p= 0.006). No episodes of hypotension or hyperkalemia were observed. Only 1 patient developed mild gynecomastia without discontinuation of the medications. Conclusion. Our study showed that hypokalemia is a prevalent problem in PD patients in Qatar. Hypomagnesemia is a significant contributing factor to hypokalemia in PD and correcting it leads to improvement of hypokalemia. Addition of spironolactone is safe and effective in treating hypokalemia. Implementing a holistic pathway led to a significant improvement in hypokalemia prevalence in PD patients.